Development of Fish Distribution Information System for Digital Virtual Assitant based on Harvesine with LoRA Node - Dwi Sasmita Aji Pambudi; Afif Zuhri Arfianto; Muhammad Khoirul Hasin; Dimas Pritovani Riananda (Indonesian Journal of Engineering Research, 2023)
The pressing issue of suboptimal and inefficient traditional fishing practices among local communities. Traditional fishermen often operate with inadequate equipment, resulting in less-than-optimal fishing outcomes. In this context, the lack of modern tools and techniques hinders the effectiveness of fish capture. Addressing these challenges is crucial for enhancing the productivity and sustainability of traditional fishing practices. The study aims to develop an advanced Fish Distribution Information System tailored for a Digital Virtual Assistant using the Haversine method and LoRA nodes. This system provide instantaneous, location-specific details about fish distribution and involves designing a data logger serving as repository for travel histories, utilizing a website as the user interface interfacing with a Leaflet map in a Geographic Information System (GIS). The Haversine method is employed for precise distance computations between LoRA Gateway, information about fish distribution, and unfavorable weather conditions within the specified area. the resukt show that The distance displayed on the website with the haversine method with excel calculation comparison produces an error calculation of 0.157%, while the percentage error for GPS latitude accuracy is 0.000116% and longitude percentage is 0.000002%. RSSI performance at LoRA ranges from -57dBM at a distance of 50m and -121dBM at a distance of 1500m.